An MCDM framework using combined compromise solution and integrated weighting method: optimizing sustainable energy options - Ng, Set Foong (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Combined Compromise Solution (CoCoSo) method is a relatively recent multiple criteria decision-making (MCDM) technique designed to address complex MCDM problems. This method evaluates and selects the optimal alternative based on multiple and often conflicting criteria. Given that criteria weights can significantly impact the decision-making process, it is crucial to devote particular attention to these weights. The aim of this study is to develop a framework to evaluate different MCDM evaluation models using the CoCoSo method, incorporating various objective weight methods and Integrated Criteria Objective Weight (ICOW) methods. A case study focusing on ranking sustainable energy options serves as the context for this MCDM problem. The study seeks to employ a comparative approach to identify the most appropriate weighting method for criteria in the CoCoSo framework. Relative Entropy Theory and the method of Lagrange Multipliers were used to derive ICOW. The case study results indicated that the MCDM model employing the ICOW method was identified as the most preferred model. The framework of CoCoSo method coupled with ICOW, along with the systematic approach in using similarity measures for ranking, offers valuable insights for MCDM practitioners and serves as a useful addition to the MCDM literature.